A fast-responding, highly sensitive detection system consisting of a fluorescent probe and palladium ions for N2H4 in environmental water and living cells. Issue 39 (24th September 2019) - Cui, Jie; Cao, Lingzhi; Wang, Guangshun; Ji, Wenjia; Nie, Hailiang; Yang, Chunliu; Zhang, Xiaoling
Abstract : A rapid and sensitive system was constructed for detecting N2 H4 in environmental water and living cells. Abstract : Hydrazine (N2 H4 ), as a chemical material and high-energy fuel, has been widely used in industry and aerospace. However, the large-scale application of N2 H4 poses a great risk to the environment and humans due to the strong corrosiveness and toxicity of N2 H4 . Herein, based on the reaction mechanisms of N2 H4 -induced Pd 2+ reduction, Pd 0 -mediated allyl cleavage and intramolecular cyclization, a new fluorescent system consisting of a probe BINC and Pd 2+ was designed for detecting N2 H4 . After adding N2 H4, the BINC–Pd 2+ system emits bright green fluorescence in less than 10 minutes, which is suitable for rapid naked-eye recognition of N2 H4 . Even when coexisting with various cations, anions, biological substances and amines, the BINC–Pd 2+ system exhibits a selective and stable fluorescence response to N2 H4 . Moreover, the fluorescence intensity at 519 nm has good linearity with the N2 H4 concentration in the range of 0–10 μM. The detection limit is 26 nM (0.83 ppb), which is lower than the threshold limit (10 ppb) of N2 H4 in drinking water. Our results indicate that the BINC–Pd 2+ system can be used for quantitative analysis of N2 H4 in environmental water with recovery rates of 95.1–103.9%, as well as fluorescence imaging of N2 H4 in living cells.